Case Report: A rare case of primary paraganglioma of the gallbladder with a literature review - Xia, Yijun; Wang, Shi; Wang, Xidong; Du, Jiya; Zhang, Lei; Xia, Long (Frontiers in Oncology, 2023)
Introduction Paragangliomas of the gallbladder are exceptionally rare. To date, only a few cases of this disease have been reported globally, and the majority were found incidentally during surgery. Although complete resection can achieve a curative effect, specific targeted drugs may have survival benefits for patients with potential recurrence and metastasis risks. Case presentation A 48-year-old woman was scheduled for anatomical central hepatectomy due to the discovery of a liver mass. Surprisingly, a gallbladder tumor accompanied by intrahepatic invasion was found rather than primary liver lesions during the operation. Postoperatively, the lesion was confirmed to be a paraganglioma originating from the gallbladder with intrahepatic invasion detectable on histopathology. After surgery, the patient was treated with a new targeted drug, surufatinib {200 mg, q.d. [quaque die (every day)]}, and no recurrence was observed during the regular follow-up. Discussion Gallbladder paraganglioma is rare and occult, and surgeons do not know it well, so it is easily misdiagnosed before surgery. Postoperative pathological examination is the gold standard for diagnosis. Conclusion Given that the tumor contained abundant blood sinuses, the early and continuous enhancement of dynamic enhanced CT scanning was its characteristic manifestation. We presented a case in which a primary gallbladder paraganglioma was identified accidentally in a patient who was misdiagnosed with a liver lesion before surgery. Based on our experience in this work, the en bloc resection technique in combination with surufatinib might have a survival benefit to patients at risk of potential recurrence or metastasis; however, further follow-up observations are needed.